1999
DOI: 10.1590/s0100-06831999000200002
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento de raízes de trigo afetado pela resistência mecânica do solo

Abstract: SUMMARYSoil compaction is a common problem that affects several soil properties and plant growth. In order to assess the effects of soil strength expressed by its mechanical resistance on roots, a growth chamber experiment was conducted at the Universidade Federal do Rio Grande do Sul, Porto Alegre, in 1994, during 35 days (530 GDD, 0ºC base temperature) on a typical Paleudult soil. Treatments, using pots arranged in a completely randomized design, consisted of soil compactions that resulted in resistances of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 15 publications
(16 reference statements)
0
3
0
3
Order By: Relevance
“…A compactação afeta o comprimento das raízes e, consequentemente, a colonização e o uso do solo, alterando a absorção de nutrientes, incorporação de água e ancoragem no solo (Merotto Jr. & Mundstock, 1999).…”
Section: Resultsunclassified
“…A compactação afeta o comprimento das raízes e, consequentemente, a colonização e o uso do solo, alterando a absorção de nutrientes, incorporação de água e ancoragem no solo (Merotto Jr. & Mundstock, 1999).…”
Section: Resultsunclassified
“…Plant rooting depth and penetration of soil are far more complex than mere possession of the genetic potential for deep root production and will be affected greatly by soil depth, soil type, and texture, and by bulk density and compaction. In many cereal crops, root elongation is reduced in proportion to the mechanical impedance of soils with significant reductions found following 2 weeks of growth when subjected to compacted soils (Ehlers, Kopke, Hesse, & Bohm, 1983; Goodman & Ennos Merotto & Mundstock, 1999). Studies in rice have identified quantitative trait loci (QTL) that are associated with differential soil penetration that shows a trade-off between root thickness and length (Price, Steele, Moore, Barraclough, & Clark, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Plant development depends on various factors, including soil quality. Resistance to penetration is one of the physical attributes of soil that limits plant growth (Letey 1985;Bengough et al 2006), and high resistance values can influence the length and diameter of roots (Merotto and Mundstock 1999;Bergamin et al 2010) depending on the species (Benghough and Mullins 1990;Silva and Rosolem 2001).…”
Section: Introductionmentioning
confidence: 99%